Estrategias digitales y su impacto en la transformación digital de las organizaciones - Delgado Debernardi, Julio Alberto (2021)
Digital transformation provides companies with greater capacity to face crises like the one we are currently experiencing with covid-19. However, it requires proper implementation. In this sense, it is necessary to investigate how digital strategies —a central element of that implementation— influence the digital transformation of organizations. The general objective is to contrast the positions of different authors regarding how digital strategies influence the digital transformations of organizations. It is a qualitative research, in which the main approaches on digital strategies and digital transformation were identified. To this end, books and journal articles from quartiles 1 and 2 of the Journal Citation Reports and Scimago were consulted; their antiquity was not greater than five years. The information has been processed using the four matrix listed in the annexes. All these parameters conform to the guidelines of the Peruvian University of Applied Sciences – UPC for the preparation of the Professional Sufficiency Work (TSP). The study shows that digital strategies are directly related to an effective digital transformation; however, its inadequate formulation and implementation can be counterproductive for the organization.